2013
DOI: 10.4038/jnsfsr.v41i2.5708
|View full text |Cite
|
Sign up to set email alerts
|

Identifying dormancy class and storage behaviour of champak (Magnolia champaca) seeds, an important tropical timber tree

Abstract: Abstract:Magnolia champaca is a culturally important tree in the tropics with a high commercial value. Its natural regeneration is rare. Hence, the species is usually propagated from seeds but with great difficulties. The class of dormancy in M. champaca seeds has been reported to be physical, physiological, and morphological. Their storage behaviour as orthodox, intermediate, and recalcitrant has been reported by various authors. During the present research, seeds of this species in Sri Lanka were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
(8 reference statements)
0
11
2
1
Order By: Relevance
“…It was found that a high level of GA 3 effectively increased shoot length, whereas a lower concentration of GA 3 inhibited shoot growth in in vitro culture of potato 45 . GA 3 has been used to break dormancy and stimulate shoot elongation in different species of magnolias for a long time [46][47][48] . In the present study, GA 3 was found to be important for bud induction, effectively shortening the time of initiation and inducing stronger buds, which is consistent with previous reports 49,50 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that a high level of GA 3 effectively increased shoot length, whereas a lower concentration of GA 3 inhibited shoot growth in in vitro culture of potato 45 . GA 3 has been used to break dormancy and stimulate shoot elongation in different species of magnolias for a long time [46][47][48] . In the present study, GA 3 was found to be important for bud induction, effectively shortening the time of initiation and inducing stronger buds, which is consistent with previous reports 49,50 .…”
Section: Resultsmentioning
confidence: 99%
“…En este estudio se encontró que las semillas de M. pugana no tienen latencia física debido a que tienen la capacidad de absorber agua. En otras investigaciones se ha sugerido la existencia de latencia mecánica, como en M. acuminata (Smith, 1990) y M. iltisiana (Saldaña-Acosta et al, 2001); o bien, morfo-fisiológica, como en M. globosa (Baskin y Baskin, 1998), M. ingrata (Han y Long, 2010a), M. biloba (Hu et al, 2011), M. officinalis (Shu et al, 2012) y M. champaca (Fernando et al, 2013), pero para M. pugana no se encontraron estos tipos de latencia.…”
Section: Discussionunclassified
“…Different studies have shown a low percentage of germination because they can present different types of dormancy (including physical, chemical, mechanical, physiological and morphological) [76]. To eliminate dormancy and increase the percentage of germination and produce the greatest number of Magnolia seedlings, different pre-germination procedures have been applied [77][78][79][80]. This section will present the research carried out in Magnolia iltisiana, M. pacifica, M. pugana and M. vallartensis, to know the viability percentages and the different most successful pregermination treatments, to break the lethargy and increase germination.…”
Section: Pre-germination Treatments and Seed Dormancymentioning
confidence: 99%